Among Traitors, Thieves, and Brokers. The Play of Intimacy in the Epistemic Economies of Cold War Intelligence Operations - Grutza, Anna (Österreichische Zeitschrift für Geschichtswissenschaften, 2023)
This article deals with the communicative interactions between actors as a crucial epistemological moment. In particular, it analyses the information exchanges and negotiations between the Polish section of the US-American Cold War broadcaster Radio Free Europe (RFE) and its Polish informants as go-betweens in the 1950s to the early 1970s. Framing these interactions as intimate epistemic economies, the author pays special attention to questions of intimacy, confidentiality, testimony, and trust as well as epistemic uncertainty regarding the identity of actors and the content of messages. Furthermore, following recent scholarship, I investigate the boundaries between the history of science and the history of knowledge by interrogating about the role of subjectivity, ignorance, error, and failure in knowledge making. Finally, two main case studies are used to exemplify the tension between different types of knowledge including rumour and gossip, in the light of the epistemic realm of un/knowledgeability in which the US and Polish secret services operated.